The Effects of TV Newscast Use in Teaching Writing for the Vocational School Students - Irfan Effendi; Ahdi Riyono (Vision: Journal for Language and Foreign Language Learning, 2017)
Writing ability is a skill that must be mastered by students. One of the media can be applied in teaching writing is TV Newscast. The objective of this research is to find out whether the writing ability of the eleventh-grade students of SMKN 1 Kudus in 2016/2017 academic year after being taught by using TV newscast is better than before. This study is experimental research; in this research, the writer used one group pre-test post-test design. There are two variables; they are TV newscast (independent variable) and the students' writing ability (dependent variable). The population of the research is the eleventh-grade students of SMKN 1 Kudus in 2016/2017 academic year. The writer used random cluster sampling as the technique to take the sample. Then XI AK 1 (accountancy class) consists of 38 students was taken. The research used achievement test as instrument for measuring the students' writing ability before and after being taught by using TV newscast and then the data were analyzed using the statistical formula. Based on the result of this research, the t0 (obtained) was higher than t-critical (20.091.56). It showed that t0 (obtained) on the critical area and the null hypothesis (H0) is rejected. Then the conclusion is that the writing ability of the eleventh-grade students of State Vocational School 1 Kudus in 2016/2017 academic year after being taught by using TV newscast is significant.